PENGARUH PENGGUNAAN MEDIA VIDEO PEMBELAJARAN UNTUK MEREDUKSI MISKONSEPSI MATEMATIKA SISWA (Integral : Pendidikan Matematika, 2022)
ABSTRACTThis study aims to: (1) determine students' mathematical misconceptions (2) determine student responses to instructional video media (3) determine the effect of using instructional video media to reduce students' mathematical misconceptions. This type of research is a mixed study with a one group pre-test post-test design. Subjects are students of class X-B MA Addzikro Putat Payung for the 2020/2021 academic year. The instrument used is a questionnaire and a CRI (Certainty of Response Index) test. The results showed: (1) the average percentage of pre-test and post-test data was 57.4% and 13.4% so that it was reduced by 44%, meaning that there was a reduction in misconceptions (2) the student response questionnaire showed a positive response, the average percentage is 74% with good category. (3) the data on the linear regression test shows the value of Sig. 0.000